Perceptions of the Influence of Project Portfolio Management on Individual Projects - AlShaikh, Meera (2014)
The influence of project portfolio management on individual projects is an issue that has caught the attention of many researchers. In this research, the researcher focused on understanding the impact of project portfolio management on individual projects using both the primary and secondary sources of data. Secondary sources of data were important in this research because it gave the researcher an insight into what other researchers have come up with in the past. This research was therefore keenly guided by the secondary sources of data. The secondary sources of data also helped in guiding the researcher on the best methodology to use when undertaking the analysis of the primary data. The primary data was collected employees of Emirates Islamic Bank. The researcher sampled a population of 50 respondents for this research to whom, the questionnaires were sent online. The researcher used quantitative research approach in data analysis for this research. The research used questionnaires to collect data from the respondents. The research also involved use of case studies in order to create a deeper understanding of the project. It is clear from the analysis of both the primary and secondary sources of data that there is a close relationship between project portfolio management and success of individual project. The secondary sources of data demonstrated that a successful management of project portfolio would result into good performance of individual project. When project portfolio management officer takes time to understand individual project and the value it gives the firm. This way, it becomes easier to allocate individual projects. As such, performance of individual projects would be influenced by project portfolio management.